Modeling the influence of complex factors on the plastic damage of a welded truss - Shved, Yaroslav; Kovalchuk, Yaroslav; Bodrova, Liudmyla; Kramar, Halyna; Shynhera, Natalya (Procedia Structural Integrity, 2024)
The paper addressed the challenge of minimizing the scattering of initial parameters in the limit state of a welded truss under the complex influence of design, technological, and operational factors. Methodologically, this objective was accomplished through a combination of full-scale, small-scale, and computer simulation experiments. The conducted experiment yielded mechanical properties of the A570-36 steel batch, displaying significantly lower dispersion of values compared to state standards and material quality certificates. Additionally, the mechanical properties of the welded samples were determined through small-scale force and computer simulation experiments on the 600x120 welded truss physical model. The computer simulation results demonstrated a reliability level of 94.6%. By compiling an input information array from the mechanical properties indicators of A570-36 steel and utilizing finite element model parameters, the simulation of the limit state parameters for a full-scale welded truss measuring 18000x3600 mm was executed. This process provided numerical, graphical, and visualized information on the truss’s limit state parameters, including maximum stresses and strains, along with their localization. Based on the research findings, a structural and technological solution was proposed to enhance the truss’s strength by 8.4%.